(untitled) (Journal of the College of Basic Education, 2022)
Education aims to expand education in all educational fields, through the educational-learning process in order to provide students with knowledge and knowledge in a better way, in order to achieve their intellectual and aesthetic development.And with the development of knowledge to high levels of accuracy, which added to the shoulders of education specialists the problem of distinguishing and differentiating between what is best and what could be an example, which allowed the logic of scientific knowledge to propose systems that are not devoid of analysis and synthesis.We find that art as a knowledge system of human knowledge requires critical analytical visions. Education and art are two interrelated and interacting topics in their knowledge systems. This is what we aim to achieve in order to benefit from art in the service of education and society.